Modeling and simulation of marine SCR system based on Modelica. (March 2023) - Shi, Jie; Zhu, Yuanqing; Peng, Hui; Yan, Haoyu; Li, Tinghui; Zhang, Jin; Zhou, Song
With the increasing awareness of global marine environmental protection, the emission of ship exhaust pollutants is strictly restricted. Selective catalytic reduction (SCR) technology is the mainstream technology to reduce ship NOx emission and make it meet IMO tier III regulations. A SCR reaction kinetic model based on Modelica language was established by Dymola software to predict the denitration efficiency, ammonia slip rate, and other parameters of SCR system. According to the functional structure of marine SCR system, the SCR system model is divided into urea injection module, mixer module, and SCR reactor module. The model was verified by SCR system bench test of WD10 diesel engine, which proved that the model can preferably reflect the actual situation. Using the established model, the effects of temperature, flow rate, NH3 /NOx Stoichiometric Ratio (NSR), and cell density on the denitration performance of SCR system were analyzed. The results showed that the exhaust gas temperature and NSR have a great influence on the denitration efficiency. The injection amount of urea solution in marine SCR system should be based on the exhaust gas temperature and exhaust flow rate.